2002
DOI: 10.1080/1364281021000041214
|View full text |Cite
|
Sign up to set email alerts
|

Electronic band structure and the X-ray photoemission spectrum of UCu<SUB>5</SUB>In

Abstract: A bstractThe family of compounds UCu 5 M (M ² Al, In or Sn) is characterized by the coexistence of magnetic order (antiferromagnetic for M ² Al and In; ferrimagnetic for M ² Sn) and Kondo lattice e ects, by moderate electronic speci®c heat enhancement (®=®0 º 8 for Al; ®=®0 º 11 for both In and Sn) and possibly a mixed-valence ground state. The electronic band structure was calculated by the tight-binding linear mu n-tin orbital method in the atomic sphere approximation. The electronic structure of UCu 5 In no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The features at 384 eV and 394.9 eV (satellite III) are often referred to as the 7 eV satellites. The presence of this kind of satellites, occurring in the 4f photoemission spectrum of many uranium intermetallic compounds, is regarded as an indication for localization of the 5f electrons [ [29,31,33], and references therein].…”
Section: Resultsmentioning
confidence: 99%
“…The features at 384 eV and 394.9 eV (satellite III) are often referred to as the 7 eV satellites. The presence of this kind of satellites, occurring in the 4f photoemission spectrum of many uranium intermetallic compounds, is regarded as an indication for localization of the 5f electrons [ [29,31,33], and references therein].…”
Section: Resultsmentioning
confidence: 99%
“…The regions exhibiting the U(6p) (−18 eV) and Sn(4d) (−25 eV) peaks are also included. Comparing the XPS valence bands of Cu and U metals [10] with the VB of the UCu 5 Sn compound, it turns out that the position of the maximum of the VB of UCu 5 Sn centred at −4 eV is shifted by 0.7 eV in the BE as compared with the VB of pure Cu. The low-energy, about 1 eV wide, peak in the valence spectrum of UCu 5 Sn is due to U(5f)-derived electrons.…”
Section: Xps Spectramentioning
confidence: 99%
“…Previously we have investigated the band structure and x-ray photoemission (XPS) of UCu 5 Al [10], crystallizing in the tetragonal structure specific for this compound [6]. We have shown that there is a possibility that in this compound the initial 5f-electron configuration has rather a complex character in the vicinity of the Fermi energy, which in consequence leads to the occurrence in the 4f-electron core spectra of a very asymmetric main line and as many as two satellites.…”
Section: Introductionmentioning
confidence: 99%
“…In the cases of systems which contained galium we have presented only U(4f 7/2 ) peak because of overlap of U(4f 5/2 ) states with Ga Auger LMM peaks. A structure consisting of the main line and the satellite located at about 7 eV higher in the BE has been observed in the XPS core-level spectra of a number of uranium intermetallic compounds [8][9][10]. The presence of this kind of satellite is an indication for a decreasing hybridization between the states of 5f and other electrons and consequently is an indication of increasing 5f-electron localization in uranium compounds.…”
Section: Methodsmentioning
confidence: 90%